Modulating the activity of human nociceptors with a SCN10A promoter-specific viral vector tool - Mouchbahani-Constance, Stephanie; Lagard, Camille; Schweizer, Justine; Labonté, Isabelle; Georgiopoulos, Miltiadis; Otis, Colombe; St-Louis, Manon; Troncy, Eric; Sarret, Philippe; Ribeiro-Da-Silva, Alfredo; Ouellet, Jean A.; Séguéla, Philippe; et al. (Neurobiology of pain, 2023)
•The NaV1.8 promoter allows the targeting of mouse nociceptors.•We designed a novel viral tool that drives expression of cargo specifically in human nociceptors.•Our viral tool enables the selective silencing of human nociceptors. Despite the high prevalence of chronic pain as a disease in our society, there is a lack of effective treatment options for patients living with this condition. Gene therapies using recombinant AAVs are a direct method to selectively express genes of interest in target cells with the potential of, in the case of nociceptors, reducing neuronal firing in pain conditions. We designed a recombinant AAV vector expressing cargos whose expression was driven by a portion of the SCN10A (NaV1.8) promoter, which is predominantly active in nociceptors. We validated its specificity for nociceptors in mouse and human dorsal root ganglia and showed that it can drive the expression of functional proteins. Our viral vector and promoter package drove the expression of both excitatory or inhibitory DREADDs in primary human DRG cultures and in whole cell electrophysiology experiments, increased or decreased neuronal firing, respectively. Taken together, we present a novel viral tool that drives expression of cargo specifically in human nociceptors. This will allow for future specific studies of human nociceptor properties as well as pave the way for potential future gene therapies for chronic pain.